TRANSPARANSI DALAM PENGELOLAAN DANA DESA (STUDI DI KECAMATAN SUKAKARYA KOTA SABANG) - Julita, Eva; Abdullah, Syukriy (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
The purpose of this study was to see whether the Sukakarya District of Sabang City had been fully or not transparent in managing village funds. The research method is quantitative research method with the census. The population in this study were all villages in Sukakarya Subdistrict, Sabang City consisting of 8 (Eight) Villages. The Data used for primary data is obtained directly without intermediaries by researchers. The Data in this research is the result of the spread of the questionnaire where the researcher distributed the data to special purpose research. The results of this study Understanding village officials related to Transparency The management of village funds in the Sukakarya District of Sabang City is already very good, because most village apparatus have fully understood what the policies of the mayor have arranged and have understood the contents of the Village Fund Management guidelines. Public perceptions related to transparency in managing village funds in general are good, except that the community still lacks perception or knowledge in managing village funds. Community participation in the process of planning and implementing village fund management is already active. This can be seen in the planning process, the people who attended were quite adequate, but there was still a lack of aspirations conveyed by the community for planning the use of village funds. Likewise in the implementation process, community participation is sufficient.